ijsr 2023
DOI: 10.36106/ijsr/6009647
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Teenage Pregnancy Its Risk Factors and Complications At the Tertiary Care Center

Abstract: Background: Pregnancy in girls between 10 and 19 years is adolescent or teenage pregnancy. Teenage parenthood comes with dangers and realities that have been well-documented. Material & Methods:This observational study was conducted at Government Medical College, AkolaMaharashtra. 80 teenage mothers admitted to the ward from October 2019 to May 2021 were included after permission from the Institutional Ethics Committee, and consent from the patients & was evaluated regarding teenage pregnancy, its risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…16 Kumar et al, assessed the relationship between mode of delivery and maternal age and concluded that age effects the mode of delivery because older women tend to have comorbidities which often end up in LSCS. 17 However, some of the studies showed that the incidence of LSCS was more in teenage mothers that is 30% as compared to adult mothers which was 15% (18). This was confirmed by our study too.…”
Section: Discussionsupporting
confidence: 82%
“…16 Kumar et al, assessed the relationship between mode of delivery and maternal age and concluded that age effects the mode of delivery because older women tend to have comorbidities which often end up in LSCS. 17 However, some of the studies showed that the incidence of LSCS was more in teenage mothers that is 30% as compared to adult mothers which was 15% (18). This was confirmed by our study too.…”
Section: Discussionsupporting
confidence: 82%